1982
DOI: 10.1038/ki.1982.66
|View full text |Cite
|
Sign up to set email alerts
|

Acid-base and metabolic responses to anion infusion in the anesthetized dog

Abstract: This study evaluated the acid-base and metabolic effects of several organic anions which might have application in the correction of metabolic acidosis during hemodialysis. Anesthetized dogs were infused intravenously with the sodium salts of either chloride, bicarbonate, acetate, lactate, or pyruvate. Acetate perturbated metabolism more than any of the other organic anions infused. These perturbations included hypoxemia, reductions in serum potassium and phosphorus, a decrease in plasma, glucose, and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…The intrave nous administration of sodium acetate in patients with end-stage renal disease is associated with hypoxemia [22]. Wathen et al [23] confirmed this observation in anesthetized dogs. Eiser et al [20] showed that acetate dialysis results in increased oxygen consumption and decreased C 0 2 production: Oh et al [17] confirmed that the reduction of respiratory quotient during acetate dial ysis is due only in minimal part to C 0 2 losses in the dia lyzer and that the most important component is a change in endogenous C 0 2 production and oxygen consump tion.…”
Section: Decreased Ventilation Due To Changes In the Endogenous Produsupporting
confidence: 65%
See 1 more Smart Citation
“…The intrave nous administration of sodium acetate in patients with end-stage renal disease is associated with hypoxemia [22]. Wathen et al [23] confirmed this observation in anesthetized dogs. Eiser et al [20] showed that acetate dialysis results in increased oxygen consumption and decreased C 0 2 production: Oh et al [17] confirmed that the reduction of respiratory quotient during acetate dial ysis is due only in minimal part to C 0 2 losses in the dia lyzer and that the most important component is a change in endogenous C 0 2 production and oxygen consump tion.…”
Section: Decreased Ventilation Due To Changes In the Endogenous Produsupporting
confidence: 65%
“…Furthermore, Sherlock et al [15] had shown an increased consumption of oxygen during dialysis which also results in changing the respiratory quotient and which cannot be related to dialyzer loss of carbon dioxide. Finally, as described below, a number of studies [17,18,22,23,25] have shown that acetate metabolism, per se, may result directly in a change in respiratory quotient which could largely explain the findings.…”
Section: Decreased Ventilation Due To Extracorporeal Losses Of Carbonmentioning
confidence: 99%
“…Lac infusion was associated with a significantly slower rate of bicarbonate level rising in comparison with Pyr, indicating that the additional metabolic steps are required [50]. The oxidation of Lac-reduced [NADH 2 ]c may take place either in cytoplasm-coupled reactions associated with gluconeogenesis, or a mitochondrial route in the presence of oxygen.…”
Section: Pyruvate Superiority In the Correction Of Acidosismentioning
confidence: 99%
“…This rate-limited step, which would display while the [NADH 2 ]c load is increased, may be another interpretation of the retardation of pHi recovery in addition to the elevated proton load, per se, from the Lac oxidation and the [NADH]c increment [10]. Although the ratio of [NAD + /NADH]c determines the balance between Pyr and Lac (equation 3), the reaction is in favor of the direction from Pyr to Lac as the lesser rise in blood Pyr concentration with Lac infusion than in blood Lac level with equal Pyr infusion [50]. Several recent findings evidently supported that Pyr would be superior to Lac in the treatment of clinic metabolic acidemia including lactic acidosis.…”
Section: Pyruvate Superiority In the Correction Of Acidosismentioning
confidence: 99%
“…This is probably due to the fact that some doubts exist on whether the method is reliable in uremic patients under dialysis. In these patients the cellular sodium-exchange system is altered [17,18], the intracellular osmolality is affected by transcellular unbalances of urea [19] and of electrolytes such as potassium [20], the use of sodium bicarbonate as buffer in the dialysate might influence transcellular distribution of sodium [21], TBW determination could be incorrect. In spite of all these putative interfering factors it has been possible to prove with our study that sodium intake may be estimated with precision by the changes in plasma sodium concentration and body water volume.…”
Section: Discussionmentioning
confidence: 99%